Exploring the use of collaborative strategies by school management teams to sustain learner discipline in secondary schools - Padayachee, Amy Sarah (University of the Free State, 2021)
Indiscipline remains a bone of contention in schools across the world. The preponderance of literature associated with indiscipline highlights its severity and the frequency of its manifestation rendering it a global problem. Literature presents a general conception of lack of discipline in South African schools. Since the post-dispensation of the education system in South Africa, school management teams have been tasked with the management of discipline in schools. Research suggests that school management teams have established, and are currently implementing, strategies to manage learner discipline. Yet, despite the implementation of these strategies, the persistence of indiscipline in schools across South Africa remains a reality. There is therefore, need for the use of strategies that can sustain learner discipline in schools. This study consequently sought to explore how school management teams use collaborative strategies to sustain learner discipline in secondary schools. This study is grounded in the Collaborative Leadership Theory. The sample size comprised 24 secondary schools in ILembe education district, from which four participants per school were selected, yielding 96 participants in total. Participants selected included the principal, one deputy principal, and two departmental heads per school. A mixed-method research approach was used for this study, and was conducted according to an explanatory sequential design. The design comprised two-phases; a quantitative and qualitative data strand. The researcher employed sequential mixed method sampling, using both probability (random) sampling and purposive sampling strategies. In the first phase, the researcher collected quantitative data by means of questionnaires. In the second phase, qualitative semi-structured interviews were used to provide further and more detailed explanations of the results obtained in the first phase. The analytical methods used included descriptive statistics for the quantitative data and content analysis for the qualitative data that was collected. The study revealed that school management teams employed strategies to manage learner indiscipline in schools by collaborating with external stakeholders and adopting a whole-school approach to sustaining learner discipline. The study also revealed that the rigidness of policy counteracts collaborative efforts. It is recommended that a collaborative leadership approach be adopted to encourage stakeholders to approach all aspects of school management in partnership with stakeholders who have a vested interest in the school.
Thesis (Ph.D. (School of Education Studies))--University of the Free State, 2021
Keywords: Collaboration; Collaborative leadership; Indiscipline; Learner discipline; Legislation; Policy; Secondary schools; Sustaining; School Management Teams